2009
DOI: 10.1109/tcsii.2009.2025629
|View full text |Cite
|
Sign up to set email alerts
|

Single-Inductor–Multiple-Output Switching DC–DC Converters

Abstract: Emerging feature dense portable microelectronic devices pose several challenges, including demanding multiple supply voltages from a single miniaturized power-efficient platform. Unfortunately, the power inductors used in magnetic-based switching converters (which are power efficient) are bulky and difficult to integrate. As a result, single-inductor-multiple-output (SIMO) solutions enjoy popularity, but not without design challenges. This brief describes, illustrates, and evaluates how SIMO dc-dc converters o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…The synchronous techniques of buck and boost converters are used for electric vehicle power supply and were presented in [11,12,14] and [15]. The multi-variable control system was designed with a single inductor for high efficiency output and was presented in [16][17][18]. The proposed research aims to address the downfalls identified in the literature review and improve the performance of the converter.…”
Section: Introductionmentioning
confidence: 99%
“…The synchronous techniques of buck and boost converters are used for electric vehicle power supply and were presented in [11,12,14] and [15]. The multi-variable control system was designed with a single inductor for high efficiency output and was presented in [16][17][18]. The proposed research aims to address the downfalls identified in the literature review and improve the performance of the converter.…”
Section: Introductionmentioning
confidence: 99%
“…On contrary, in the switched capacitor implementation, the efficiency is not dramatically affected and the chip active area is larger than the one used by the linear regulator solution because the secondary converter control required a complex logic circuit [24]. Finally, the conventional SIBO approach provides high efficiency with a decrease of the die area by using a single time-shared inductor [26]. The conventional SIBO converter is part of the conventional Single-Inductor Multiple-Output (SIMO) switching converter family [23], which basic topology is depicted in Figure 1b.…”
Section: Introductionmentioning
confidence: 99%
“…The conventional SIBO converter is part of the conventional Single-Inductor Multiple-Output (SIMO) switching converter family [23], which basic topology is depicted in Figure 1b. Topologically, conventional SIMO converters are circuit extrapolations of the corresponding Single-Inductor Single-Output (SISO) converters, except that energy flow and feedback control are more complex [26]. Furthermore, a voltage variation in one output affects the other ones because they share a common inductor [23,27].…”
Section: Introductionmentioning
confidence: 99%
“…This is primarily because it excels at simplifying the power conditioning process while improving source utilization [6,7]. MPC research was initially oriented towards a wide array of lower-power applications, such as telecommunications [8], micro-electronics [9], and EV/HEVs [10], but has more recently expanded into higher-power applications, such as wind and solar [11,12].…”
Section: Introductionmentioning
confidence: 99%